Possíveis correlações entre o hormônio tireoidiano e depressão do tipo ansiosa em ratos obesos - Lorena, Fernanda Beraldo [UNIFESP] (2017)
Obesity is related to memory and learning processes impairment, as well as the depressive and anxious behavior. The thyroid hormone (TH) modulates the development and functioning of the CNS by regulating the expression of genes related to brain plasticity. The same genes regulated by T3 are changed in obesity. The literature describes the relationship between thyroid hormone and mood changes such as depression and anxiety that may generally be reversed by treatment with T3. Thus, our working hypothesis is based on the possibility that changes in T3 signaling in the brain of obese rats may be involved with changes in the functioning of the CNS observed in obesity. To test our hypothesis we treat male Wistar rats with high fat diet (40%) by 32 weeks. At the end of this period, the animals were subjected to behavioral testing to assess the acquisition memory capacity and the presence of anxious and depressive behavior in obese animals. We also evaluated changes in the expression of genes involved in depression, genes involved in the availability of T3 in the brain and genes regulated by T3. Through behavioral tests, we found that obesity induces a depressive and anxious behavior, but does not lead to memory impairment. The gene expression analysis showed that obesity leads to increased expression of TH transporters, receptors for TH (TRs) and lower expression of genes positively regulated by T3, Aldh1a1 and RBM3, and increased Halpln1, a gene negatively regulated . It is possible that obese individuals show a lower availability of T3 in the brain, which induces a local moderate hypothyroidism and possibly changes in the pathway signaling of this hormone are a compensatory mechanism. Furthermore, we observed a significant increase in the expression of genes related to inflammation, which may also be associated with the phenotype found in these animals. In summary, our results suggest that there is a change in TH signaling in the brain that may be involved in the development of a depressed and anxious phenotype induced by obesity.